Pengembangan Model Pembelajaran Portofolio Service Learning dalam Mata Pelajaran Pendidikan Kewarganegaraan di SD Laboratorium UNG - Aina Nurdiyanti; Andi Marshanawiah (Journal on Education, 2023)
A study conducted in relation to the citizen involvement index shows that the education system has a central role in forming a base of volunteerism which in the long term will become social capital in the form of positive behavior of citizens towards national development. In the Canadian curriculum, specifically in Ontario, 40 hours of community service is a prerequisite for students to graduate from high school (Brown et al, 2007). If we compare this system with that in Indonesia, the question that will arise is how often do schools or classrooms program community service activities for their students? This research was conducted to develop a learning program based on service learning as an effort to strengthen the Pancasila character of students in elementary schools. Learning experiences gained through community service activities can catalyze personal development and contribute to the development of more responsible young citizens, especially in the basic education phase. This research includes development research (Research & Development with ADDIE (Analysis, Design, Development, Implementation, and Evaluation) design (Branch, 2009). The results of the research show that UNG Laboratory Elementary School requires a service learning portfolio learning model in Civics subjects for personality development students, especially aspects of social care which are more participatory. The results of the design and development of the service learning portfolio prototype by researchers have obtained expert validation with a feasibility value of 93% in the Very Feasible category. Thus, the service learning portfolio learning model in citizenship education subjects has been successful developed and ready to be implemented in a limited trial for further assessment of its level of success